2016
DOI: 10.1155/2016/8424931
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Case-Series Study Comparing the Stability of Implant with Two Different Surfaces Placed in Fresh Extraction Sockets and Immediately Loaded

Abstract: Background. Hydrophilic and moderately rough implant surfaces have been proposed to enhance the osseointegration response. Aim. The aim of this study was to compare early changes of stability for two implants with identical macrodesign but with different surface topographies. Materials and Methods. In 11 patients, a total of 22 implants (11 bimodal (minimally rough, control) and 11 proactive (moderately rough and hydrophilic, test), Neoss Ltd., Harrogate, UK) were immediately placed into fresh extraction socke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
4
4
0
Order By: Relevance
“…Increased stability favours also predictability of immediate- or early loading protocols. The fact that all implants that had an extremely low IT and very low ISQ values at baseline because of split crest, sinus floor elevation, GBR-procedures or combinations of those led to complete integration confirms the biocompatibility and osteoconductivity of the ProActive surface as reported by other authors [37]. In all those cases RFA monitoring revealed increasing ISQ values from baseline to the 6 and 12 month follow-up registrations, which indicate a favourable bone tissue response to the implants.…”
Section: Discussionsupporting
confidence: 82%
“…Increased stability favours also predictability of immediate- or early loading protocols. The fact that all implants that had an extremely low IT and very low ISQ values at baseline because of split crest, sinus floor elevation, GBR-procedures or combinations of those led to complete integration confirms the biocompatibility and osteoconductivity of the ProActive surface as reported by other authors [37]. In all those cases RFA monitoring revealed increasing ISQ values from baseline to the 6 and 12 month follow-up registrations, which indicate a favourable bone tissue response to the implants.…”
Section: Discussionsupporting
confidence: 82%
“…This is an improvement compared with a previous study from our group using the same implant but with a different and smoother surface (Neoss Bimodal) where 5% more failures were seen in the GBR group . It is possible that the present rougher surface, produced by blasting and acid etching (Neoss ProActive), resulted in a stronger bone response as also demonstrated in previous studies . Moreover, a clinical follow‐up study on early loading of full‐arch constructions showed clear differences in favor of the Neoss ProActive surface .…”
Section: Discussionmentioning
confidence: 51%
“…6 It is possible that the present rougher surface, produced by blasting and acid etching (Neoss ProActive), resulted in a stronger bone response as also demonstrated in previous studies. 8,19,20 Moreover, a clinical follow-up study on early loading of full-arch constructions showed clear differences in favor of the Neoss ProActive surface. 9 The present surface has also been chemically modified to increase wettability, which means that it is rapidly soaked in blood during placement.…”
Section: Discussionmentioning
confidence: 99%
“…The ISQ values were calculated during the placement and loading (4 months after placement) [14]. The mean difference in ISQ values was 2.18 ± 0.28 which was statistically significant ( p = 0.00).…”
Section: Resultsmentioning
confidence: 99%